Effect of Employee Creativity and Emotional Intelligence on Entrepreneurship Orientation - Nurhaedah Adnin Rasyad; S. Sapar (Yayasan Ahmar Cendekia Indonesia, 2022)
This study examines managers' emotional intelligence and employee creativity in entrepreneurial orientation in SMEs. This research method uses a quantitative approach. The population of this research is all MSMEs in three sub-districts, namely Wara, East Wara, and North Wara Districts. The sample of this research is 137 MSME Managers. This research was conducted in December 2021. The instrument used was a questionnaire using a structural equation modeling (SEM) approach with the help of the smart PLS 3.3 application. The results of this study indicate that managers' emotional intelligence affects the entrepreneurial orientation of SMEs by 0.074 units with a t count = 0.377 < t table = 1.972 or a P-value of 0.706 > 0.05. Employee creativity has an effect on entrepreneurial orientation by 0.414 units with a T arithmetic value = 2.665 > T table 1.972 with a P-value of 0.008 <0.05. The joint influence of a manager's emotional intelligence and employee creativity on entrepreneurial orientation is 19.1%, while the remaining 81.9% influence other variables.